Kreativitas Ramah Lingkungan: Pelatihan Anyaman Bambu bagi Siswa SD untuk Membangun Kesadaran Keberlanjutan - Ernes Septina Azizi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This study aimed to enhance sustainability awareness through eco-friendly creativity by introducing bamboo weaving training to elementary school students at SDN 3 Karangkobar. The training integrated cultural heritage with practical skills, emphasizing environmental conservation. The program involved sixth-grade students in hands-on activities, teaching them to transform bamboo into functional crafts. Findings revealed high enthusiasm from both students and teachers, highlighting the program's potential to foster creativity, entrepreneurial spirit, and environmental responsibility. The training also underscored the importance of utilizing local resources and preserving traditional crafts. Despite challenges such as limited materials and facilities, this initiative demonstrated the feasibility of embedding sustainability principles in education. Recommendations include curriculum adjustments to integrate local wisdom-based art education and increased support for creative, environment-focused learning methods.